Resource Sharing in Support of Continuing Education An Exploratory Survey - Grupe, Fritz H.; Stewart, Mary; Associated Colleges of the St. Lawrence Valley, Potsdam, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Resource sharing among institutions as a method of supporting continuing education is surveyed. The following three trends are identified: the growth of continuing education, experimentation with consortial approaches to higher education, and continued emphasis on cost effectiveness. Among the objectives of the survey were to determine what cooperative projects existed and where they were located through review of the Educational Resources Information Center (ERIC) and from data provided by Title I administrators, to produce an inventory of the projects identified and divide the inventory into subgroups, and finally to determine ways in which the cooperative projects related to the goals of continuing education and cost effectiveness. Descriptions of projects in nine categories--planning and needs assessment, promotion and publicity, counseling, media, curriculum/instructional materials, special populations, community development, extension centers, and staff development--are presented. The cost benefits of consortia and continuing education are explored, including such areas as avoidance of unnecessary duplication, distribution of risk, and entry to funding agencies. An inventory of cooperative/continuing education programs and a brief bibliography are appended. (PHR)
Availability: Associated Colleges of the St. Lawrence Valley, Raymond Hall, State University College at Potsdam, Potsdam, NY 13676.
Sponsoring Agency: New York State Education Dept., Albany.
Educational level discussed: Adult Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Community Development; Consortia; Continuing Education Centers; Cooperative Planning; Cooperative Programs; Coordination; Cost Effectiveness; Counseling; Directories; Educational Cooperation; Educational Trends; Higher Education; Institutional Cooperation; Instructional Materials; Lifelong Learning; Needs Assessment; Publicize; Resources; Shared Services; Staff Development; Surveys; Reports, Research; Reference Materials, Directories/Catalogs.